Fetal hemodynamic response to aortic valvuloplasty and postnatal outcome: a European multicenter study. (27th June 2018) - Kovacevic, A.; Öhman, A.; Tulzer, G.; Herberg, U.; Dangel, J.; Carvalho, J. S.; Fesslova, V.; Jicinska, H.; Sarkola, T.; Pedroza, C.; Averiss, I. E.; Mellander, M.; et al.
ABSTRACT: Objective: Fetal aortic stenosis may progress to hypoplastic left heart syndrome. Fetal valvuloplasty (FV) has been proposed to improve left heart hemodynamics and maintain biventricular (BV) circulation. The aim of this study was to assess FV efficacy by comparing survival and postnatal circulation between fetuses that underwent FV and those that did not. Methods: This was a retrospective multicenter study of fetuses with aortic stenosis that underwent FV between 2005 and 2012, compared with contemporaneously enrolled natural history (NH) cases sharing similar characteristics at presentation but not undergoing FV. Main outcome measures were overall survival, BV‐circulation survival and survival after birth. Secondary outcomes were hemodynamic change and left heart growth. A propensity score model was created including 54/67 FV and 60/147 NH fetuses. Analyses were performed using logistic, Cox or linear regression models with inverse probability of treatment weighting (IPTW) restricted to fetuses with a propensity score of 0.14–0.9, to create a final cohort for analysis of 42 FV and 29 NH cases. Results: FV was technically successful in 59/67 fetuses at a median age of 26 (21–34) weeks. There were 7/72 (10%) procedure‐related losses, and 22/53 (42%) FV babies were delivered at < 37 weeks. IPTW demonstrated improved survival of liveborn infants following FV (hazard ratio, 0.38; 95% CI, 0.23–0.64; P = 0.0001), after adjusting for circulation and postnatal surgical center. Similar proportions had BV circulation (36% for the FV cohort and 38% for the NH cohort) and survival was similar between final circulations. Successful FV cases showed improved hemodynamic response and less deterioration of left heart growth compared with NH cases ( P ≤ 0.01). Conclusions: We report improvements in fetal hemodynamics and preservation of left heart growth following successful FV compared with NH. While the proportion of those achieving a BV circulation outcome was similar in both cohorts, FV survivors showed improved survival independent of final circulation to 10 years' follow‐up. However, FV is associated with a 10% procedure‐related loss and increased prematurity compared with the NH cohort, and therefore the risk‐to‐benefit ratio remains uncertain. We recommend a carefully designed trial incorporating appropriate and integrated fetal and postnatal management strategies to account for center‐specific practices, so that the benefits achieved by fetal therapy vs surgical strategy can be demonstrated clearly. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.